IDENTIFIKASI Candida Sp. SWAB VAGINA PEKERJA SEKS KOMERSIAL DI KAWASAN GEROKGAK KABUPATEN BULELENG, BALI: Array (Midwinerslion : Jurnal Kesehatan STIKes Buleleng, 2018)
Diseases caused by fungal infections are one of the diseases that are still a health problem in Indonesia. Fungal infections can be divided into superficial and deep infections. Among the superficial infections that are often transmitted through sexual intercourse are infections by Candida sp. This study aims to determine Candida species obtained from vaginal swabs of commercial sex workers in the Gerokgak area of ​​Buleleng Regency, Bali. This research is a descriptive type of research with the samples used are commercial sex workers in Gerokgak, Buleleng Regency, Bali who meet the inclusion criteria. The sample size in this study used a total sampling method in which all populations were sampled as many as 30 people and only met the inclusion criteria of 25 people. Vaginal discharge was then identified by the germ tube test method. The results showed that 15 samples (60%) were positive including Candica albicans and 10 samples (40%) were negative.